Phytochemistry PREPARATION OF DIFFERENT CRUDE EXTRACT AND ANTIMICROBIAL STUDIES OF SPIROGYRA RHIZOPUS: Preparation of crude extracts and Bioactivity studies - DANIEL E; GIRMA T; VENKATESAN JAYAKUMAR S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The importance of this work is to prepare the crude extracts of Spirogyra rhizopus and to study the biological activity of crude extract against four bacterial strains. Materials and Methods: Spirogyra algae collected from Jimma town, and crude extracts were prepared by cold percolation method and sonication method and further analyzed for qualitative phytochemical analysis. The efficacy of crude extracts is tested for bacterial activity by disc-diffusion method. Results: The maximum zone of inhibition shown by the crude extract is compared to standard and control. Among the four extracts, chloroform extract displayed the promising inhibitory action against four bacterial strains. Conclusions: The preliminary study concludes that green algae S. rhizopus is a potential source of pharmacologically active lead molecules. In vitro screening of crude extracts of green algae S. rhizopus shows promising activity against bacterial strains and thus suggests its application in drug discovery research.